Klastry jako instrument działania samorządów w zakresie kreowania regionalnych i lokalnych specjalizacji gospodarczych - case study "Dolina lotnicza" - Prusek, Andrzej (Cluster as an Instrument of Local Governments in the Creation of Regional and Local Economic Specializations, 2007)
The goal of the paper is an analysis of industry and innovation clusters as the local government instrument of regional development and creation of regional and local economic specializations. The paper presents the meaning of cluster "Dolina lotnicza" and its influence on the Podkarpackie region development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 215-228